2015
DOI: 10.1038/nature16483
|View full text |Cite
|
Sign up to set email alerts
|

The C. elegans adult neuronal IIS/FOXO transcriptome reveals adult phenotype regulators

Abstract: Insulin/IGF-1 signaling (IIS) is a critical regulator of an organism’s most important biological decisions, from growth, development, and metabolism to reproduction and longevity. It primarily does so through the activity of the DAF-16/FOXO transcription factor, whose global targets were identified in C. elegans using whole-worm transcriptional analyses more than a decade ago1. IIS and FOXO also regulate important neuronal and adult behavioral phenotypes, such as the maintenance of memory2 and axon regeneratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
311
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(328 citation statements)
references
References 34 publications
15
311
2
Order By: Relevance
“…Transcriptional profiling of adult PLM neurons has detected expression of several genes in the piRNA pathway, including prde-1 and prg-1 (Kaletsky et al, 2016; Lockhead et al, 2016). Thus, we asked whether prde-1 mRNAs could be visualized in PLM neurons using smFISH (single-molecule fluorescence in situ hybridization), which allows detection of single mRNAs in cells (Raj et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptional profiling of adult PLM neurons has detected expression of several genes in the piRNA pathway, including prde-1 and prg-1 (Kaletsky et al, 2016; Lockhead et al, 2016). Thus, we asked whether prde-1 mRNAs could be visualized in PLM neurons using smFISH (single-molecule fluorescence in situ hybridization), which allows detection of single mRNAs in cells (Raj et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Together, these results suggest that the function of PRG-1/PIWI in eliminating target mRNAs by endonucleolytic cleavage could be responsible for target gene silencing in somatic cells. By mining published TRN transcriptomes (Kaletsky et al, 2016; Lockhead et al, 2016) and piRNA target database (Bagijn et al, 2012), we identified numerous candidate target mRNAs for piRNA in TRN neurons (see STAR methods and Table S2). Further studies will be required to elucidate specific targets of the neuronal piRNA pathway critical for axon regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In such times of nutrient shortage, expression of insulin receptor homologs such as DAF-2 is low. The sole C. elegans FoxO homolog, DAF-16, is therefore not phosphorylated and is thus able to enter the nucleus and transactivate its targets, a full list of which was recently published (Kaletsky et al, 2016). The effect of DAF-16 on longevity is primarily manifested in the intestine (Murphy et al, 2007;Libina et al, 2003), and its effects on lifespan are likely to be related to the regulation of genes involved in countering oxidative and thermal stress (Nemoto and Finkel, 2002).…”
Section: Foxo In C Elegansmentioning
confidence: 99%
“…A recent study delineated the neural targets of DAF-16 in C. elegans by comparing the transcriptomes of neurons that had been FACS sorted from wild type and insulin signaling-deficient (daf-16;daf-2) mutants (Kaletsky et al, 2016). Since many FoxO targets are conserved from C. elegans to humans (Webb et al, 2016), it has been proposed that understanding the mechanisms by which FoxO regulates aging in the nematode might provide a basis for extending human lifespan.…”
Section: Foxo In C Elegansmentioning
confidence: 99%
“…The enhanced regeneration of daf-2 and daf-18 mutants requires the DLK-1 pathway, and DAF-16/FOXO itself may regulate dlk-1 transcription. Transcriptional profiling of neurons has also identified the forkhead factor fkh-9 as a target of DAF-16 required for daf-2-dependent adult axon regeneration (Kaletsky et al 2016). C. elegans should be a tractable model to explore how age affects axon regenerative capacity.…”
Section: Developmental Timing and Aging: Micrornas And Insulin Signalingmentioning
confidence: 99%